2021
DOI: 10.1111/inm.12975
|View full text |Cite
|
Sign up to set email alerts
|

Exploring mental health clinicians' perceptions of the Zero Suicide Prevention Initiative

Abstract: Suicide continues to impact rural and regional families and communities across Australia and has become a key focus of healthcare, research, and government policy in recent years. The challenge for healthcare organizations is to translate policy visions and research for clinicians to effectively embed in day to day practice when supporting people who experience suicidal crisis. This study explored the introduction of an evidence-based Zero Suicide framework that includes a suicide prevention pathway and traini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…The difference is the HOPE team receives these types of referrals more frequently than the other mental health teams. The qualitative analysis of this project identified that mental health clinicians from a variety of teams required regular, ongoing suicide prevention education that was tailored to their area of practice [ 16 ]. Even still, areas of improvement identified for the HOPE team include further exploration of the behavioural incident (events over the prior 48 h) and further exploring context and details of suicidal behaviour including location.…”
Section: Discussionmentioning
confidence: 99%
“…The difference is the HOPE team receives these types of referrals more frequently than the other mental health teams. The qualitative analysis of this project identified that mental health clinicians from a variety of teams required regular, ongoing suicide prevention education that was tailored to their area of practice [ 16 ]. Even still, areas of improvement identified for the HOPE team include further exploration of the behavioural incident (events over the prior 48 h) and further exploring context and details of suicidal behaviour including location.…”
Section: Discussionmentioning
confidence: 99%